PENGARUH PEMANFAATAN MULTIMEDIA ARTICULATE STORYLINE TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK - Dani, Ali Umar; Arief, Syaifuddin (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
The purpose of this study is to describe the learning outcomes of physics after being taught using articulate storyline-based multimedia learning, to describe the learning outcomes of physics before being taught using multimedia articulate storyline-based learning, to analyze the improvement of learning outcomes before and after the application of multimedia articulate storyline-based learning to learning outcomes. physics. This type of research is a pre-experimental design with one group pretest posttest design. The subjects in this study were students of class X MIA 1 SMAN 9 Luwu Timur in the academic year 2021-2022. The data collection technique used purposive sampling technique. The instrument used is a test of learning outcomes. The results of the descriptive analysis showed that the average value of the pretest of learning outcomes was 46.18. While the average value of posttest learning outcomes is 76.22. The results of inferential analysis based on the results of statistical calculations of paired t test, it is known that tcount -17.454 and ttable with df of 26 is 2.056. The comparison between tcount and ttable is -tcount -17.454 < -ttable -2.056 with a probability value (sig) of 0.00 less than 0.005. From this comparison, it can be concluded that H1 is accepted and H0 is rejected, this means that there is an increase in learning outcomes from pretest to posttest after being given treatment.